2007
DOI: 10.1097/01.prs.0000252505.52821.76
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Keloid Scars with Three-Dimensional Imaging: Quantifying Response to Intralesional Steroid Therapy

Abstract: Three-dimensional stereophotogrammetry is a rapid and noninvasive method of scar volume assessment that could allow accurate and objective monitoring of treatment response to be incorporated into clinical practice. Therefore, it can be of considerable value in assessing treatment efficacy and evaluating new therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 19 publications
2
54
0
Order By: Relevance
“…Corticosteroid injections, which are applied intralesionally and reduce scar volume by decreasing inflammation, increasing vasoconstriction, and inhibiting fibroblast proliferation, are associated with significant side effects. The development of steroid tapes and plasters has significantly improved the effect of steroid injections when used in combination [7,8]. Besides, stem cell based treatment such as mesenchymal stem cells, hematopoietic stem cells, and skin-derived precursors in wound healing is progressively being valued, but more protracted studies are needed to determine whether the observed effects are clinically significant [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid injections, which are applied intralesionally and reduce scar volume by decreasing inflammation, increasing vasoconstriction, and inhibiting fibroblast proliferation, are associated with significant side effects. The development of steroid tapes and plasters has significantly improved the effect of steroid injections when used in combination [7,8]. Besides, stem cell based treatment such as mesenchymal stem cells, hematopoietic stem cells, and skin-derived precursors in wound healing is progressively being valued, but more protracted studies are needed to determine whether the observed effects are clinically significant [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid injections rapidly reduce the volume of a scar 28 . However, the downsides of corticosteroid injections include pain (caused by the injection itself) and difficulties associated with contraindications such as pregnancy, glaucoma, or Cushing's disease.…”
Section: Corticosteroid Tapes/plastersmentioning
confidence: 99%
“…After treating the patients for a minimum of 8 weeks, the majority of patients achieved a greater than 50% response with a mean (SD) scar volume at the start of 0.73 (0.701) mL reduced to 0.14 (0.302) mL. 3 Chowdri et al 4 reviewed their experience with 58 keloids and hypertrophic scars using intralesional corticosteroid injection. After doing serial injections at weekly intervals for 2 to 5 weeks followed by monthly injections for 4 to 6 months, more than 90% of the patients had no evidence of a recurrence at a mean follow-up of 30.5 months.…”
Section: Nonsurgical Therapy Corticosteroidsmentioning
confidence: 99%
“…Repeated injections are often required and are typically performed at 2-to 4-week intervals, with the total number of injections depending on the response and possible adverse effects. Ardehali et al 3 objectively monitored the response of keloids to intralesional triamcinolone acetate injections using 3-dimensional imaging. After treating the patients for a minimum of 8 weeks, the majority of patients achieved a greater than 50% response with a mean (SD) scar volume at the start of 0.73 (0.701) mL reduced to 0.14 (0.302) mL.…”
Section: Nonsurgical Therapy Corticosteroidsmentioning
confidence: 99%